Rate of shed of SARS COV-2 viral RNA from COVID-19 cadavers. Issue 12 (December 2022) - Sharma, Meenakshi; Brijwal, Megha; Chakraborty, Nabarun; Choudhary, Aashish; Kumar, Arbind; Srivastav, Sharad; Lalwani, Parin; Agrawal, Richa; Dev Soni, Kapil; Madaan, Nirupam; Malhotra, Rajesh; Mathur, Purva; et al.
Abstract: Background: At what rate does the RNA of SARS CoV-2 shed from cadavers? Although, there have been numerous studies which have demonstrated the persistence of the virus on dead bodies, there is a lack of conclusive evidence regarding the variation of viral RNA content in cadavers. This has led to a knowledge gap regarding the safe handling/management of COVID-19 decedents, posing a barrier in forensic investigations. Methods: In this study, we report the presence of RNA of SARS CoV-2 by real time RT-PCR, in nasopharyngeal swabs collected after death from two groups of bodies – one who died due to COVID-19 and the other who died due to other diagnoses. A prospective study on 199 corpses, who had tested positive for COVID-19 ante-mortem, was conducted at a tertiary care center. RNA testing was conducted at different time intervals (T1-T5). Results: 112(56.3%) died primarily due to COVID-19 and 87(43.7%) died due to other diagnoses. 144(72.4%) were male and 55(27.6%) were female. A total of 115 (57.8%) tested positive for COVID-19 after death at different time points. The mean age was 50.7 ± 18.9 years and the length of hospitalization ranged from 1 to 50 days with a mean of 9.2 ± 7.6 days. Realtime RT-PCR positivity of SARS CoV-2 RNA decreases with time. Conclusion: We observed that real time RT-PCR positivity, indicating viral RNA detection, decreases with time. Therefore, it is advisable to follow appropriate COVID-19 precautions to carry out scientific studies, medico-legal investigations and mortuary services on suspected/confirmed COVID-19 corpses. Highlights: Lack of conclusive evidence on the persistence of SARS CoV-2 virus on corpses. Realtime RT-PCR positivity of SARS CoV-2 RNA decreases with time. Safe handling and management of confirmed/suspected COVID-19 positive cadavers.